FINANCIAL PERFORMANCE AND CSR IN SOUTHEAST ASIA COUNTRIES LISTED BEVERAGE FIRMS - Nagoro, Damar Panuluh; Nainggolan, Yunieta Anny (Journal of Business and Management, 2018)
Abstract. The present world conditions are based on a report from the UN development goals of 2017, improving both on water quality and world energy use to achieve sustainability goals by 2030. Corporate sustainability reporting provides important information for investors including the company's views on environmental issues and sustainability as well as environmental and social mitigation strategies and opportunities to take advantage. Can also be presented influence on financial performance (Krechowicz & Fernando, 2009). This research analyze is there any correlation between corporate sustainability especially on environmental issues (material, water and energy) and financial performance (Stock price, EBIT, NOPAT, and Tobin’s Q) of southeast Asia stock market (Indonesia, Malaysia, Singapore, Thailand, Philippines and Vietnam). This research gives insight and recommendations for the investors in choosing stocks for investment based on environmental performance in materials, energy and water used of the beverage companies. This thesis has scope in Southeast Asia include Indonesia, Malaysia, Singapore, Thailand, Vietnam and Philippines. According to the result of the regression estimation, Total CSR Score is positively significant to Stock Price, EBIT and NOPAT of beverages companies in southeast Asia. It is accordance with (Pettenella, 2010) that said CSR can reduce direct cost that will impact company’s earnings and CSR have significant effect to company’s stock price (De Klerk, de Villiers, & van Staden, 2015). It indicates that all beverages companies should pay more attention to CSR especially in water, energy and material.Keywords: CSR, Energy, Water, Material, Stock Price, EBIT, Tobin’s Q